A STUDY ON TEACHERS' EFFORTS IN MOTIVATING STUDENTS TO LEARN ENGLISH AT GRADE VIII OF SMPN 1 TEMBILAHAN HULU - Indah Indriyah; Maizarah; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2021)
The problem of this research was that students' motivation in learning English is good, so it is needed to know what teacher's effort in motivating them. Therefore, the purpose of this research is to know what teachers’ efforts in motivating students to learn English at grade VIII of SMPN 1 Tembilahan Hulu are. Therefore, this research was descriptive quantitative research. The researcher distributed the questionnaire to twenty students of the eighth grade of excellent class and interviewed the English teacher as a sample to know what teachers' efforts in motivating Students to learn English. The sample was taken using total sampling because there are only twenty students and one teacher for an excellent class. After collecting the data, the researcher found that teacher has reasonable effort in motivating students to learn English. The efforts are teacher uses various activities in teaching, prepares some engaging media, gives students assignment based on what they have learned, relates topics in teaching to students' daily activities, asks the students to think about their experience, gives reword to students, says positive words, gives students a chance to present their course work, and gives memorable score when students finish group work soon. Therefore, students can be motivated to learn when their teacher keeps supporting them by making some efforts in teaching.